Menstrual problems and mental health issues: exploring the propinquity among adolescent girls in private high schools of Mysuru - N., Renuka; Kulkarni, Praveen; Shabadi, Nayanabai; B. C., Sunil; M. R., Narayana Murthy (International Journal Of Community Medicine And Public Health, 2022)
Background: Menstruation is a normal physiological process that begins during adolescence and may be associated with various symptoms with their onset, before, during or after the menstrual flow. Menstrual problems are generally perceived as an only minor health concern and thus given less importance. This study aimed to find the relationship between menstrual problems and mental health. Methods: Cross sectional study was conducted to find out the relationship between the menstrual problems and mental health issues among school going students in the age group of 13 – 16 years. 320 adolescent girls of randomly selected high schools located in Mysuru were studied by self-administered pretested semi structured questionnaire. Results: Among 320 adolescent girls included in the present study, 93% had one or other kind of menstrual problems. Prevalence of dysmenorrhea, menorrhagia, irregular cycles, premenstrual syndrome, and amenorrhea were 55%, 43%, 14.4%, 52.8% and 5% respectively. Prevalence of stress, depression and anxiety were 35%, 66.2% and 62.8% respectively. There was a statistically significant association between dysmenorrhea, anxiety, and stress. Conclusion: Prevalence of menstrual problems as well as mental health problems was found to be high among adolescent girls. There was a significant association between dysmenorrhea, anxiety, and stress. Thus, there is a need to undertake regular screening activities for the adolescent girls on both menstrual and mental health problems in order to detect them early and provide essential support.